2023
DOI: 10.1111/jhn.13230
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vegetarian diet on sperm quality, sex hormone levels and fertility: a systematic review and meta‐analysis

Abstract: BackgroundAn increasing number of people have adhered to vegetarian diet since several years ago. Nowadays, the favorable effect of this dietary pattern on metabolic diseases is well established, but its impact on fertility and reproductive health as a serious health concern is not clear yet.Hence, we aim to summarize existing evidence, regarding the possible association between a vegetarian diet, and fertility as measured by key indicators such as sperm quality, and sex hormone levels.MethodsWe systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Conversely, a vegan diet eliminates all animal products. The consequences of a vegetarian or vegan diet on fertility are still debated [122]. From one point of view, the possible lack of some nutrients, such as iron or essential fatty acids, could increase the risk of infertility.…”
Section: Vegetarian and Vegan Dietmentioning
confidence: 99%
“…Conversely, a vegan diet eliminates all animal products. The consequences of a vegetarian or vegan diet on fertility are still debated [122]. From one point of view, the possible lack of some nutrients, such as iron or essential fatty acids, could increase the risk of infertility.…”
Section: Vegetarian and Vegan Dietmentioning
confidence: 99%
“…Lim et al [ 45 ] observed in a cohort of 805 Asian women, who reported their dietary data on FFQs, that those with a higher adherence to a healthy plant-based diet (higher vegetable and fruit intake) took less time to get pregnant than the women who followed an unhealthy plant-based diet (high intake of fast food and sugary drinks). Finally, a recent meta-analysis examined sex hormone levels and concluded that it was not possible to associate the vegetarian diet with a positive or negative effect on fertility and reported only a reduction in estrone levels in the vegetarian population [ 46 ].…”
Section: Dietsmentioning
confidence: 99%
“…Some studies have observed better sperm quality in vegan men compared to nonvegan men [ 49 ], and others have indicated lower quality [ 50 ]. Moreover, a recent meta-analysis reported no conclusive effect of a vegetarian diet on semen characteristics [ 46 ].…”
Section: Dietsmentioning
confidence: 99%